How Can Phenomenology Be Preserved in the Study of Religion? A Proposal - Kirsberg, Igor W. (2019)
This paper provides a foundation for a form of phenomenology, namely phenomenological, that rejects the traditional phenomenology of religion in order to provide a cognitive and non-theological discipline in the study of religion. Proposed amendments to phenomenology are based on the ideas of E. Husserl. The simultaneous strict distinction and necessary cooperation between facts and phenomena provided by the impurity of pure consciousness in admitting the outside world might enable the extension of scientific criteria to this reimagined phenomenology. Pure consciousness is considered irreducible to thought and cognitivity (feeling and accordingly, faith, might thus be viewed as a non-cognitive, purely emotional stream). This new comprehension of the phenomenology of religion could represent religion in all its contexts (God, supernatural forces as well as holy places, churches, utensils, texts etc) in the pure consciousness of the believer, as the effects of its structures, namely feeling and thought and their interactions and peculiarities.
Keywords: faith experience; Phenomenology; phenomenology of religion; Pure Consciousness; study of religion